Remote sensing applications for planning irrigation management. The use of SEBAL methodology for estimating crop evapotranspiration in Cyprus - Papadavid, George; Perdikou, Paraskevi N.; Hadjimitsis, Michalakis; Hadjimitsis, Diofantos G. (My University, 2014)
Water allocation to crops has always been of great importance in the agricultural process. In this context, and under the current conditions, where Cyprus is facing a severe drought the last five years, the purpose of this study is basically to estimate the needed crop water requirements for supporting irrigation management and monitoring irrigation on a systematic basis for Cyprus using remote sensing techniques. The use of satellite images supported by ground measurements has provided quite accurate results. Intended purpose of this paper is to estimate the Evapotranspiration (ET) of specific crops which is the basis for irrigation scheduling and establish a procedure for monitoring and managing irrigation water over Cyprus, using remotely sensed data from Landsat TM/ ETM and a sound methodology used worldwide, the Surface Energy Balance Algorithm for Land (SEBAL).
Keywords: Water management; Accuracy assessment; Algorithm; Evapotranspiration; Irrigation; Landsat thematic mapper; Remote sensing; Satellite imagery; Ιrrigation management; SEBAL